The cults of Kalydon: Reassessing the miniaturised votive objects - Barfoed, Signe (Proceedings of the Danish Institute at Athens, 2017)
The purpose of this article is to cast further light on the religious cults of the city of Kalydon and Kalydonian ritual behaviour. Excavations in 2001-05 and 2011-16 have produced a substantial amount of miniature votive pottery, and in drawing attention to this hitherto rather overlooked aspect of material culture, I will argue that it must play an important role in our understanding of religious practice in ancient Kalydon. Within the last decade miniature pottery has attracted considerable scholarly attention, which has produced insight that may be applied to the evidence from Kalydon. Both published and unpublished miniature pottery is contextualized, and the cult related to the miniature votives is re-examined. Kalydon’s most famous cult is to Artemis Laphria, but two additional cults have been identified during the recent excavations: a shrine on the central Acropolis, and the cult in the Peristyle House in the Lower Town.